Auxilio! Tenemos poderes extranos! - Stine, R. L. (New York : Scholastic, 2013)
Read each other's thoughts. But that's not all. They can read other people's thoughts, too! The strange new powers are exciting...at first. But soon they discover that a weird scientist knows their secret and wants to control their powers.
Jillian y Jackson se asombran cuando descubren que pueden leer la mente y mover objetos con solo concentrarse. Pero muy pronto pasan a sentir terror cuando descubren que un extrano cientifico conoce su secreto y pretende controlar sus poderes.
8-12 anos.
Accelerated Reader
Keywords: Psychic ability -- Juvenile fiction; Twins -- Juvenile fiction; Aptitud psiquica -- Novela juvenil; Mellizos -- Novela juvenil